The impact of teacher feedback on students’ decisions to stay on or change course after math failure in a Confucian cultural context - Fwu, Bih-Jen; Yang, Tong-Rong; Chen, Yi-Kai; Chen, Rong (Frontiers in Psychology, 2022)
Rattan et al.’s (2012) research indicated that instructors holding entity belief tended to judge students to have low ability and provided ability-comforting feedback following math failure. Students receiving such feedback tended to quit and change course, creating a potential decrease in the pool of students pursuing math related fields. In Confucian heritage cultures (CHCs), the ideal society is primarily based on fulfillment of duties. Thus, Rattan et al.’s ability-based findings, derived from WEIRD samples, may not apply to duty-based CHCs. We hypothesized that CHC’s teachers holding obligation belief tend to attribute students’ failure to lack of duty fulfillment and provide duty-based feedback, including duty-comforting and duty-advising feedback, which motivates students to stay on rather than change course. To validate our hypothesis, we conducted three scenario experiments with 160 college students with teaching experiences, 273 high school students, and 369 pre-service teachers in Taiwan. Results showed that while ability-based paradigm may be culture-free, duty-based paradigm seems to be culture-bound. Consistent with Rattan et al.’s research, teachers with entity belief tended to give ability-comforting feedback, pushing students to pursue non-math related fields. In contrast, teachers with obligation belief were likely to offer duty-comforting and duty-advising feedback, contributing to students’ persistent pursuit in math. Furthermore, three fifths of teachers were inclined to provide ability-comforting, duty-comforting and duty-advising feedback concurrently, thus putting students in an unpleasant predicament that might be detrimental to their psychological well-being. Theoretical and practical implications are discussed.